Virtual experiments of Physics using Scilab - Sharma, Smita (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
There are certain areas of Physics where different experimental phenomena are explained using some theoretical concepts. It is often said that a certain theory is able to reproduce experimental results. Some of them can be verified easily, but some theories have very complex computations that cannot be solved easily, and so end results are shown directly by graphs, final values, etc. But as Richard P. Feynman[1] said „What I cannot create, I do not understand‟, here we have tried to design experiments using theoretical concepts by writing simple programs, that allow students to observe the results and finally verify them by the available results. All this has been done using Scilab, which is open-source scientific computation software that can be used to perform numerical computations. It is easy to use even for people that have no previous programming experience. In this paper we have explained one such virtual experiment which is related to the study of the linear harmonic oscillator in which the student is able to observe the variation produced in the oscillation when mass and spring constant is varied and damping is introduced. Students can visualize each variation produced and interpret the result in a very easy manner. Several other experiments can also be designed by students themselves and make concept learning easier.